Graphene conductive paste and preparation method and application thereof

By using modified silane coupling agent in graphene conductive paste, the problems of insufficient conductivity, dispersion and corrosion resistance are solved, and the conductivity, dispersion, adhesion, viscosity, corrosion resistance and thermal stability are significantly improved, and are suitable for a variety of battery applications.

CN119673529AInactive Publication Date: 2025-03-21CTRON ADVANCED MATERIAL CO LTD

Patent Information

Application Number
CN202510178736.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing graphene conductive paste has shortcomings in corrosion resistance, conductivity, viscosity performance and dispersion, which affects its stability and service life.

Method used

Using a modified silane coupling agent, the 6-fluoro-2-aminophenol group is grafted onto the silane coupling agent KH-560 through the ring opening reaction of amino groups and epoxy groups, and reacts with dimethylphosphoric acid to form a modified silane coupling agent. The structure of the modified silane coupling agent contains fluorine elements, phenolic hydroxyl groups and phosphorus elements, which improves the dispersion, binding force and corrosion resistance of the conductive paste.

Benefits of technology

The conductive properties, dispersion, adhesion, viscosity, corrosion resistance and thermal stability of graphene conductive paste are significantly improved, so that it can show excellent performance in lead-acid batteries, sodium ion batteries, lithium ion batteries and other applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_3
    Figure SMS_3
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of conductive materials, and particularly discloses graphene conductive paste and a preparation method and application thereof. The graphene conductive paste is prepared from the following raw materials in parts by weight: 1 to 10 parts of graphene, 0.5 to 10 parts of conductive carbon black, 0.5 to 1 part of a dispersing agent, 0.5 to 2 parts of a stabilizer, 80 to 90 parts of a solvent, 0.5 to 1.5 parts of a surfactant, 1 to 5 parts of a modified silane coupling agent and 0.5 to 1 part of an adhesive, the molecular structure of the modified silane coupling agent contains fluorine element and phosphorus element, and also contains phenolic hydroxyl group, and various groups have synergistic interaction, so that the performance of the graphene conductive paste is improved together; the invention also discloses a preparation method and application of the graphene conductive paste. The graphene conductive paste provided by the invention has excellent conductivity, cohesiveness, corrosion resistance, dispersity and thermal stability, and can be widely applied to preparation of lead-acid batteries, sodium-ion batteries and lithium-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of conductive materials, and in particular to a graphene conductive slurry and a preparation method and application thereof. Background Art

[0002] Graphene conductive paste is a high-performance electronic material, mainly composed of graphene, conductive fillers, organic carriers and functional additives. The core lies in the introduction of graphene, which is a two-dimensional material composed of a single layer of carbon atoms tightly arranged in a hexagonal lattice. Due to its excellent electrical conductivity, high thermal conductivity, excellent mechanical strength and chemical stability, it has broad application prospects in the field of electronic materials.

[0003] The patent with application number CN202310270301.5 discloses a conductive slurry and its preparation method and application, including the following components in weight: 1-8 parts of conductive functional material, 0.5-3 parts of dispersant, 0-1 part of surfactant, 15-40 parts of anti-settling liquid, and 60-90 parts of solvent. The conductive functional material includes carbon nanotubes (including first carbon nanotubes, second carbon nanotubes and third carbon nanotubes, the first carbon nanotubes have a length of 20-40μm and a diameter of 15-20nm, the second carbon nanotubes have a length of 41-60μm and a diameter of 10-15nm, and the third carbon nanotubes have a length of 61-80μm and a diameter of 6-10nm) and graphene; the application improves the dispersion stability of the conductive slurry by combining carbon nanotubes with different aspect ratios, gives full play to its conductive properties, and forms a conductive network with carbon nanotubes as conductive bridges and uniform dispersion, but the corrosion resistance needs to be improved. Insufficient corrosion resistance will directly affect the stability and service life of the product. The patent with application number CN202211385580.1 discloses a method for preparing a graphene composite carbon nanotube conductive slurry. The invention first prepares oxidized carbon nanotubes and oxidized graphene, reacts the oxidized carbon nanotubes with thionyl chloride and 3-aminopropyltriethoxysilane in sequence to obtain modified carbon nanotubes, reacts the oxidized graphene with monochloroacetic acid to obtain modified graphene, premixes nano-copper powder and modified graphene, and then mixes them with modified carbon nanotubes, organic solvents, and polyethersulfone resin to obtain a graphene composite carbon nanotube conductive slurry; the graphene composite carbon nanotube conductive slurry prepared by the invention has good wear resistance and corrosion resistance, but the conductivity, viscosity and dispersibility of the prepared conductive slurry need to be further improved.

[0004] Therefore, it is necessary to develop a graphene conductive paste with excellent dispersibility, conductivity, corrosion resistance, thermal stability and bonding properties, which is of great significance for expanding the application of conductive paste. Summary of the invention

[0005] The purpose of the present invention is to provide a graphene conductive paste and a preparation method and application thereof in view of the deficiencies in the prior art. The graphene conductive paste prepared by the present invention has excellent conductivity, dispersibility and bonding properties and has corrosion resistance and thermal stability.

[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: A graphene conductive slurry comprises the following raw materials in parts by weight: 1-10 parts of graphene, 0.5-10 parts of conductive carbon black, 0.5-1 parts of dispersant, 0.5-2 parts of stabilizer, 80-90 parts of solvent, 0.5-1.5 parts of surfactant, 1-5 parts of modified silane coupling agent, and 0.5-1 part of adhesive; the preparation method of the modified silane coupling agent is as follows: Step S1, adding 6-fluoro-2-aminophenol and silane coupling agent KH-560 to anhydrous ethanol at 40-60° C. with stirring, reacting for 2-4 hours, cooling to room temperature, and removing the solvent to obtain an intermediate; Step S2, adding the intermediate obtained in step S1, aluminum chloride and dimethyl phosphoric acid to N,N-dimethylformamide at 100-110° C. with stirring, reacting for 5-7 hours, cooling to room temperature, and obtaining a modified silane coupling agent after purification; The synthetic route of modified silane coupling agent is as follows: .

[0007] Furthermore, in step S1, the mass ratio of 6-fluoro-2-aminophenol to silane coupling agent KH-560 is 1:1.5-2.5, and the amount of 6-fluoro-2-aminophenol added to anhydrous ethanol is 0.08-0.15 g / mL.

[0008] Furthermore, in step S2, the mass ratio of the intermediate, aluminum chloride and dimethyl phosphoric acid is 3:0.06-0.075:1-2, and the amount of dimethyl phosphoric acid added to N,N-dimethylformamide is 0.1-0.15 g / mL.

[0009] Furthermore, the dispersant is one or more of sodium stearate, polyvinyl alcohol, polyethylene imine, potassium p-sulfonate acetoacetanilide, and polyethylene glycol.

[0010] Furthermore, the stabilizer is one or more of sodium carboxymethyl cellulose, polyacrylic acid, and polyvinyl pyrrolidone.

[0011] Furthermore, the solvent is one or more of N-methylpyrrolidone, deionized water, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl succinate, dibutyl phthalate, ethanol, isopropanol, butanone, and toluene.

[0012] Furthermore, the surfactant is one or more of sodium n-octadecyl sulfate, sodium dodecylbenzene sulfonate, sodium lignin sulfonate, and hexadecyltrimethylammonium bromide.

[0013] Furthermore, the adhesive is one or more of styrene-butadiene rubber, ethyl cellulose, polyvinylidene fluoride, and polytetrafluoroethylene.

[0014] The present invention also provides a method for preparing a graphene conductive slurry, comprising the following steps: (1) mixing graphene, conductive carbon black, a dispersant, a stabilizer, a surfactant, a modified silane coupling agent, and a binder, and ball milling to obtain a dry powder; (2) The dry powder obtained in step (1) and the solvent are first mixed and then sand-milled to obtain a graphene conductive slurry.

[0015] The above graphene conductive slurry is used in the preparation of lead-acid batteries, sodium-ion batteries and lithium-ion batteries.

[0016] The present invention has the following beneficial effects: The invention prepares the modified silane coupling agent by a chemical modification method. First, a 6-fluoro-2-aminophenol group is grafted onto a silane coupling agent KH-560 through a ring-opening reaction between an amino group and an epoxy group to obtain an intermediate. Then, a hydroxyl group of the intermediate reacts with dimethyl phosphoric acid to generate a modified silane coupling agent. The modified silane coupling agent contains a fluorine element in its structure. The low surface tension property of the fluorine element helps the conductive paste system to better wet the surfaces of inorganic materials and organic materials, thereby improving the dispersibility and bonding force of the conductive paste. The modified silane coupling agent also contains a phenolic hydroxyl group in its structure. The phenolic hydroxyl group has hydrophilicity and lipophilicity, which makes the conductive paste The material can show good dispersibility in both water and oily media; in addition, the modified silane coupling agent structure also contains phosphorus, which can react with other elements in the conductive paste to form a dense protective film, which can isolate corrosive substances in the external environment, thereby protecting the conductive paste from corrosion; in addition, fluorophosphorus compounds have high thermal stability and chemical stability, and can maintain the performance of the paste stable under high temperature and harsh environment, and extend the service life of the paste. Fluorophosphorus compounds can also increase the connection between the conductive particles in the paste, forming a more effective conductive network, thereby reducing the resistivity of the paste.

[0017] The present invention obtains graphene conductive paste after compounding graphene, conductive carbon black, dispersant, stabilizer, solvent, surfactant, adhesive and modified silane coupling agent, wherein the modified silane coupling agent contains two groups of different chemical properties in the molecular structure at the same time, including Si-O-Si group and organic group, and the two groups of different properties can form a "molecular bridge" between inorganic material and organic material, thereby enhancing the binding force of the two materials, and then improving the adhesion of the conductive paste; the modified silane coupling agent can also improve the dispersion uniformity of the two conductive materials, graphene and conductive carbon black, in the paste, thereby improving the conductivity of the paste, reducing resistance, and enhancing the conduction efficiency of the current. The graphene conductive paste prepared by the present invention has excellent conductivity, dispersibility, adhesion, viscosity, corrosion resistance and thermal stability, and can be widely used in lead-acid batteries, sodium ion batteries, and lithium ion batteries. DETAILED DESCRIPTION

[0018] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0019] The raw materials used in the following examples are all common commercial products. The surface area of ​​conductive carbon black is 1300-1600m² / g, the oil absorption value is 3-3.50ml / g, the tinting power is 110-140%, the particle size D50 is 15-20nm, and the ash content is 0.8-1%; polyvinyl alcohol is polyvinyl alcohol 2488, purchased from Jinan Guangxun Trading Co., Ltd.; polyethyleneimine has a viscosity of 200-500mPa·s and a molecular weight of 300; polyethylene glycol has a molecular weight of 400; sodium carboxymethyl cellulose has a viscosity of 50-100mPa·s and a molecular weight of 90000; the effective ingredient content of polyacrylic acid is 99%, purchased from Qingdao Baiyi Chemical Co., Ltd.; polyvinyl pyrrolidone is PVP K15 model was purchased from Lianyungang Ronghe New Material Technology Co., Ltd.; SBR1502 model was selected for styrene-butadiene rubber, purchased from Xiangmao International Trade (Changzhou) Co., Ltd.; N-20 model was selected for ethyl cellulose, with a mesh size of 100, purchased from Hebei Kelongduo Biotechnology Co., Ltd.; Arkema HSV900 model was selected for polyvinylidene fluoride, purchased from Shanghai Xinjihua Plastic Co., Ltd.; and PFA345X was selected from Chemours, USA, purchased from Dongguan Jiangyu New Materials Co., Ltd.

[0020] Example 1 A graphene conductive slurry comprises the following raw materials in parts by weight: 1 part of graphene, 10 parts of conductive carbon black, 0.5 parts of a dispersant, 0.5 parts of a stabilizer, 80 parts of a solvent, 0.5 parts of a surfactant, 1 part of a modified silane coupling agent, and 0.5 parts of an adhesive; The dispersant is sodium stearate, the stabilizer is sodium carboxymethyl cellulose, the solvent is N-methyl pyrrolidone, the surfactant is sodium n-octadecyl sulfate, and the binder is styrene-butadiene rubber; The preparation method of the modified silane coupling agent is as follows: Step S1, adding 1 g of 6-fluoro-2-aminophenol and 1.5 g of silane coupling agent KH-560 to 12.5 mL of anhydrous ethanol at 40° C. with stirring, reacting for 4 hours, and then drying in a vacuum drying oven at 40° C. to constant weight to obtain an intermediate; Step S2, adding 3 g of the intermediate obtained in step S1, 0.06 g of aluminum chloride and 1 g of dimethyl phosphoric acid to 10 mL of N,N-dimethylformamide at 100° C. with stirring, reacting for 7 h, cooling to room temperature and filtering to obtain a filtrate, then rotary evaporating the filtrate at a temperature of 80° C., a rotation rate of 120 rpm and a vacuum degree of 25-50 mbar to remove N,N-dimethylformamide to obtain a modified silane coupling agent.

[0021] The synthetic route of modified silane coupling agent is as follows: ; The NMR results of the modified silane coupling agent are: 1 H NMR (300 MHz, acetone-d6) δ 9.58 (s, 1H), 8.99 (s, 1H), 6.71-6.77 (m, 1H), 6.58-6.66 (m, 1H), 6.40-6.52 (m, 1H), 3.75-3.81 (m, 2H), 3.50-3.56 (m, 11H), 3.25-3.35 (m, 3H), 1.36-1.45 (m, 2H), 1.26 (d, 6H), 0.56 (t, 2H).

[0022] A method for preparing a graphene conductive slurry comprises the following steps: (1) Graphene, conductive carbon black, dispersant, stabilizer, surfactant, modified silane coupling agent and binder were mixed and ball-milled at 400 rpm for 1.5 h to obtain dry powder; (2) The dry powder obtained in step (1) and the solvent are first placed in a blender, stirred at 1000 rpm for 5 min, and then placed in a 30 Hz sand mill for 2 h to obtain a graphene conductive slurry.

[0023] Example 2 A graphene conductive slurry comprises the following raw materials in parts by weight: 10 parts of graphene, 1 part of conductive carbon black, 1 part of dispersant, 2 parts of stabilizer, 90 parts of solvent, 1.5 parts of surfactant, 5 parts of modified silane coupling agent, and 1 part of adhesive; The dispersant is polyvinyl alcohol, the stabilizer is polyacrylic acid, the solvent is N,N-dimethylformamide, the surfactant is sodium dodecylbenzene sulfonate, and the binder is ethyl cellulose; The preparation method of the modified silane coupling agent is as follows: Step S1, adding 1 g of 6-fluoro-2-aminophenol and 2.5 g of silane coupling agent KH-560 to 6.67 mL of anhydrous ethanol at 60° C. with stirring, reacting for 2 h, and then drying in a vacuum drying oven at 40° C. to constant weight to obtain an intermediate; Step S2, adding 3 g of the intermediate obtained in step S1, 0.075 g of aluminum chloride and 2 g of dimethyl phosphoric acid to 13.33 mL of N,N-dimethylformamide at 110° C. with stirring, reacting for 5 h, cooling to room temperature and filtering to obtain a filtrate, then rotary evaporating the filtrate at a temperature of 80° C., a rotation rate of 120 rpm and a vacuum degree of 25-50 mbar to remove N,N-dimethylformamide to obtain a modified silane coupling agent.

[0024] A method for preparing a graphene conductive slurry comprises the following steps: (1) Graphene, conductive carbon black, dispersant, stabilizer, surfactant, modified silane coupling agent and binder were mixed and ball-milled at 400 rpm for 1.5 h to obtain dry powder; (2) The dry powder obtained in step (1) and the solvent are first placed in a blender, stirred at 1000 rpm for 5 min, and then placed in a 30 Hz sand mill for 2 h to obtain a graphene conductive slurry.

[0025] Example 3 A graphene conductive slurry comprises the following raw materials in parts by weight: 5 parts of graphene, 6 parts of conductive carbon black, 0.7 parts of a dispersant, 1 part of a stabilizer, 85 parts of a solvent, 1 part of a surfactant, 3 parts of a modified silane coupling agent, and 0.8 parts of a binder; The dispersant is polyethylene glycol, the stabilizer is polyvinyl pyrrolidone, the solvent is dimethyl succinate, the surfactant is sodium lignin sulfonate, and the adhesive is styrene-butadiene rubber; The preparation method of the modified silane coupling agent is as follows: Step S1, adding 1 g of 6-fluoro-2-aminophenol and 2 g of silane coupling agent KH-560 to 10 mL of anhydrous ethanol at 50° C. with stirring, reacting for 3 h, and then drying in a vacuum drying oven at 40° C. to constant weight to obtain an intermediate; Step S2, adding 3 g of the intermediate obtained in step S1, 0.07 g of aluminum chloride and 1.5 g of dimethyl phosphoric acid to 12.5 mL of N,N-dimethylformamide at 105° C. with stirring, reacting for 6 h, cooling to room temperature and filtering to obtain a filtrate, then rotary evaporating the filtrate at a temperature of 80° C., a rotation rate of 120 rpm and a vacuum degree of 25-50 mbar to remove N,N-dimethylformamide to obtain a modified silane coupling agent.

[0026] A method for preparing a graphene conductive slurry comprises the following steps: (1) Graphene, conductive carbon black, dispersant, stabilizer, surfactant, modified silane coupling agent and binder were mixed and ball-milled at 400 rpm for 1.5 h to obtain dry powder; (2) The dry powder obtained in step (1) and the solvent are first placed in a blender, stirred at 1000 rpm for 5 min, and then placed in a 30 Hz sand mill for 2 h to obtain a graphene conductive slurry.

[0027] Comparative Example 1 A graphene conductive slurry comprises the following raw materials in parts by weight: 5 parts of graphene, 6 parts of conductive carbon black, 0.7 parts of a dispersant, 1 part of a stabilizer, 85 parts of a solvent, 1 part of a surfactant, 3 parts of a modified silane coupling agent, and 0.8 parts of a binder; The dispersant is polyethylene glycol, the stabilizer is polyvinyl pyrrolidone, the solvent is dimethyl succinate, the surfactant is sodium lignin sulfonate, and the adhesive is styrene-butadiene rubber; The preparation method of the modified silane coupling agent is as follows: 1 g of 6-fluoro-2-aminophenol and 2 g of silane coupling agent KH-560 are added to 10 mL of anhydrous ethanol at 50° C. under stirring conditions, react for 3 hours, and then place in a vacuum drying oven at 40° C. to dry to constant weight to obtain a modified silane coupling agent.

[0028] A method for preparing a graphene conductive slurry comprises the following steps: (1) Graphene, conductive carbon black, dispersant, stabilizer, surfactant, modified silane coupling agent and binder were mixed and ball-milled at 400 rpm for 1.5 h to obtain dry powder; (2) The dry powder obtained in step (1) and the solvent are first placed in a blender, stirred at 1000 rpm for 5 min, and then placed in a 30 Hz sand mill for 2 h to obtain a graphene conductive slurry.

[0029] Comparative Example 2 A graphene conductive slurry comprises the following raw materials in parts by weight: 4 parts of graphene, 4 parts of conductive carbon black, 0.5 parts of a dispersant, 0.3 parts of a stabilizer, 80 parts of a solvent, 0.2 parts of a surfactant, 1 part of a silane coupling agent KH-560, and 0.5 parts of a binder; The dispersant is polyethylene glycol, the stabilizer is polyvinyl pyrrolidone, the solvent is dimethyl succinate, the surfactant is sodium lignin sulfonate, and the adhesive is styrene-butadiene rubber; A method for preparing a graphene conductive slurry comprises the following steps: (1) Graphene, conductive carbon black, dispersant, stabilizer, surfactant, silane coupling agent KH-560 and binder were mixed and ball-milled at 400 rpm for 1.5 h to obtain dry powder; (2) The dry powder obtained in step (1) and the solvent are first placed in a blender, stirred at 1000 rpm for 5 min, and then placed in a 30 Hz sand mill for 2 h to obtain a graphene conductive slurry.

[0030] Comparative Example 3 A graphene conductive slurry comprises the following raw materials in parts by weight: 1 part of graphene, 0.5 part of conductive carbon black, 0.1 part of dispersant, 0.3 part of stabilizer, 80 parts of solvent, 0.4 part of surfactant, and 0.5 part of binder; The dispersant is polyethylene glycol, the stabilizer is polyvinyl pyrrolidone, the solvent is dimethyl succinate, the surfactant is sodium lignin sulfonate, and the adhesive is styrene-butadiene rubber; A method for preparing a graphene conductive slurry comprises the following steps: (1) Graphene, conductive carbon black, dispersant, stabilizer, surfactant and binder were mixed and ball-milled at 400 rpm for 1.5 h to obtain dry powder; (2) The dry powder obtained in step (1) and the solvent are first placed in a blender, stirred at 1000 rpm for 5 min, and then placed in a 30 Hz sand mill for 2 h to obtain a graphene conductive slurry.

[0031] The properties of the graphene conductive slurries prepared in Examples 1-3 and Comparative Examples 1-3 were tested. The testing method is as follows. The test results are shown in Tables 1 and 2 below.

[0032] (1) Adhesion Adhesion was measured according to GB / T17473.4-2008.

[0033] (2) Viscosity The test was carried out according to the rotational viscometer method described in DB13 / T5026.1-2019.

[0034] (3) Conductive properties The square resistance was measured according to GB / T17473.3-2008.

[0035] (4) Dispersion performance The fineness is measured according to GB / T17473.2-2008.

[0036] (5) Corrosion resistance Take 5 mL of the graphene conductive slurry obtained in each embodiment and comparative example, apply it into a coating of the same size, shape and thickness and sinter it at 120° C. for 10 min, polish it to the same roughness and weigh it, soak the surface in 10 mL of a 5% hydrochloric acid aqueous solution at room temperature for 20 min, then rinse the surface with ethanol, dry it and weigh it, and the mass difference before and after the acid treatment is the corrosion amount.

[0037] (6) Thermal stability The graphene conductive paste obtained in each embodiment and comparative example was placed in a high temperature environment of 120°C for 100 hours, and the square resistance (mΩ / ) of the film formed by sintering the graphene conductive paste at 120°C for 10 minutes was tested every 10 hours using a multifunctional four-probe tester.

[0038] Table 1 Adhesion, viscosity, conductivity, dispersion and corrosion resistance tests of graphene conductive slurry sample Adhesion (N) Viscosity (mPa.s) Square resistance (Ω / ) Fineness (μm) Corrosion amount (g) Example 1 5.6 2560 6.15 <5 0.11 Example 2 5.9 2710 5.89 <5 0.12 Example 3 5.5 2603 6.07 <5 0.12 Comparative Example 1 4.9 2587 10.63 <7 0.36 Comparative Example 2 4.6 2533 12.25 <7 0.49 Comparative Example 3 3.2 2500 13.04 <9 0.50 Table 2 Thermal stability test of graphene conductive paste sample 10h 20h 30h 40h 50h 60h 70h 80h 90h 100h Example 1 6.20 6.25 6.36 6.44 6.49 6.54 6.60 6.67 6.73 6.81 Example 2 5.98 6.03 6.11 6.18 6.25 6.33 6.39 6.49 6.58 6.66 Example 3 6.21 6.29 6.36 6.44 6.51 6.60 6.65 6.72 6.81 6.90 Comparative Example 1 10.81 10.89 10.97 11.05 11.16 11.23 11.38 11.46 11.59 11.71 Comparative Example 2 12.48 12.72 12.99 13.26 13.91 14.10 14.51 14.97 15.63 16.34 Comparative Example 3 13.41 13.89 14.46 15.03 15.47 16.05 16.87 17.24 17.91 18.36 It can be seen from Table 1 and Table 2 that the graphene conductive pastes prepared in Examples 1-3 have excellent performance and a wider range of applications. As can be seen from Table 1, the adhesion of the graphene conductive paste prepared in Examples 1-3 is better than that in Comparative Examples 1-3, which helps to make the conductive paste more firmly adhere to the surface of the material when used. This is because the silane coupling agent of the embodiment is modified and the fluorine element is introduced, so that the conductive paste prepared in the embodiment has a stronger bonding force when used, thereby improving the adhesion; the square resistance of the graphene conductive paste prepared in Examples 1-3 is also relatively small, and the conductive performance is better. The square resistance of the conductive paste prepared in Comparative Examples 2 and 3 is relatively large because there is no silane coupling agent containing fluorine and phosphorus elements in these two conductive pastes, resulting in poor conductive performance of the conductive paste; the fineness of the graphene conductive paste prepared in Examples 1-3 is also relatively small, the dispersibility is good, it is not easy to agglomerate when used, and it is more convenient to use, while the conductive paste prepared in Comparative Examples 2 and 3 does not have fluorine elements and phenolic hydroxyl groups, has poor dispersibility, and is easy to agglomerate, which also has an adverse effect on the conductive performance of the conductive paste. It can be seen from Table 1 and Table 2 that the graphene conductive paste prepared in Examples 1-3 has good corrosion resistance and thermal stability, can maintain good performance in harsh environments, and extend its service life, while the conductive paste prepared in Comparative Examples 1-3 does not introduce a silane coupling agent containing a fluorophosphorus compound, and therefore has poor corrosion resistance and thermal stability.

[0039] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0040] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A graphene conductive slurry, characterized in that: The invention comprises the following raw materials in parts by weight: 1-10 parts of graphene, 0.5-10 parts of conductive carbon black, 0.5-1 parts of dispersant, 0.5-2 parts of stabilizer, 80-90 parts of solvent, 0.5-1.5 parts of surfactant, 1-5 parts of modified silane coupling agent, and 0.5-1 parts of adhesive; the preparation method of the modified silane coupling agent is as follows: Step S1, adding 6-fluoro-2-aminophenol and silane coupling agent KH-560 to anhydrous ethanol at 40-60° C. with stirring, reacting for 2-4 hours, cooling to room temperature, removing anhydrous ethanol, and obtaining an intermediate, the structural formula of the intermediate is: ; Step S2, adding the intermediate obtained in step S1, aluminum chloride and dimethyl phosphoric acid to N,N-dimethylformamide at 100-110° C. with stirring, reacting for 5-7 hours, cooling to room temperature, and obtaining a modified silane coupling agent after purification. The structural formula of the modified silane coupling agent is: 。 2. The graphene conductive paste according to claim 1, characterized in that: The mass ratio of 6-fluoro-2-aminophenol to silane coupling agent KH-560 in step S1 is 1:1.5-2.5, and the amount of 6-fluoro-2-aminophenol added to anhydrous ethanol is 0.08-0.15 g / mL.

3. The graphene conductive paste according to claim 1, characterized in that: The mass ratio of the intermediate, aluminum chloride and dimethyl phosphoric acid in step S2 is 3:0.06-0.075:1-2, and the amount of dimethyl phosphoric acid added to N,N-dimethylformamide is 0.1-0.15 g / mL.

4. The graphene conductive paste according to claim 1, characterized in that: The dispersant is one or more of sodium stearate, polyvinyl alcohol, polyethylene imine, potassium p-sulfonate acetoacetanilide, and polyethylene glycol.

5. The graphene conductive paste according to claim 1, characterized in that: The stabilizer is one or more of sodium carboxymethyl cellulose, polyacrylic acid and polyvinyl pyrrolidone.

6. The graphene conductive paste according to claim 1, characterized in that: The solvent is one or more of N-methylpyrrolidone, deionized water, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl succinate, dibutyl phthalate, ethanol, isopropanol, butanone and toluene.

7. The graphene conductive paste according to claim 1, characterized in that: The surfactant is one or more of sodium n-octadecyl sulfate, sodium dodecylbenzene sulfonate, sodium lignin sulfonate, and hexadecyltrimethylammonium bromide.

8. The graphene conductive paste according to claim 1, characterized in that: The adhesive is one or more of styrene-butadiene rubber, ethyl cellulose, polyvinylidene fluoride and polytetrafluoroethylene.

9. A method for preparing the graphene conductive paste according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) mixing graphene, conductive carbon black, a dispersant, a stabilizer, a surfactant, a modified silane coupling agent, and a binder, and ball milling to obtain a dry powder; (2) The dry powder obtained in step (1) and the solvent are first mixed and then sand-milled to obtain a graphene conductive slurry.

10. Use of the graphene conductive slurry according to any one of claims 1 to 8 in the preparation of lead-acid batteries, sodium-ion batteries, and lithium-ion batteries.

Citation Information

Patent Citations

  • Preparation method of graphene composite carbon nanotube conductive paste

    CN115831442A

  • Conductive paste and preparation method and application thereof

    CN116417179B

  • Hydrophobic metallic oxide powder, producing method and toner composition for electrophotograph

    CN101196700A

  • Nano chitosan derivative and preparation method and application thereof

    CN101575384A

  • Graphene lithium battery conductive paste

    CN107871871A

Cited By

  • Graphene-based lithium ion battery conductive paste and preparation method thereof

    CN121687838A